Cochrane Database of Systematic Reviews 2010
DOI: 10.1002/14651858.cd007514.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Statins for the treatment of dementia

Abstract: There is insufficient evidence to recommend statins for the treatment of dementia. Analysis from the studies available, including one large RCT, indicate statins have no benefit on the outcome measures ADAS-Cog or MMSE. We need to await full results from CLASP 2008 before we can be certain. This Cochrane review will be updated as these results become available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 88 publications
1
97
0
3
Order By: Relevance
“…Thus, dementia may be influenced by high total cholesterol. However, it is not clear whether or not cholesterol lowering medication, such as statin treatment, in midlife is beneficial for dementia [21]. Furthermore, information on the use of cholesterol lowering medication in the follow-up period was not available in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, dementia may be influenced by high total cholesterol. However, it is not clear whether or not cholesterol lowering medication, such as statin treatment, in midlife is beneficial for dementia [21]. Furthermore, information on the use of cholesterol lowering medication in the follow-up period was not available in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Serum cholesterol level shows a positive correlation with the incidence of stroke, and high cholesterol level in middle age, decreased high-density lipoprotein (HDL) cholesterol levels, and increased LDL cholesterol levels are associated with cognitive dysfunction in the aged [38]. Low levels of HDL cholesterol and high levels of LDL cholesterol could be risk factors for coronary heart disease and carotid artery atherosclerosis, which may lead to cognitive impairment by cerebral hypoperfusion [39].…”
Section: Applications To Other Dementiasmentioning
confidence: 99%
“…A Cochrane review also described that there were no studies supporting the role of statins for treatment of VD [38]. Thus, the effectiveness of statins for VD is still controversial, but possible statins could provide protection from VD if taken from young or middle age.…”
Section: Applications To Other Dementiasmentioning
confidence: 99%
“…Statin therapy has been evaluated in several clinical trials. Meta-analysis of several large prospective clinical trials revealed no significant benefits of atorvastatin or simvastatin therapy in patients with dementia who had been treated for periods ranging from 26 to 72 weeks, despite significant reductions in serum low density lipoprotein (LDL) (228)(229)(230)(231). Still, other studies showed significant reductions in incident dementia among statin users (232,233).…”
Section: Radical Scavengers-epidemiological Studies Suggested That Lomentioning
confidence: 99%